Do gifts buy votes? Evidence from sub-Saharan Africa - Jenny Guardado; Leonard Wantchekon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Vote-buying-or the pre-electoral distribution of private goods in exchange for support at the ballot box-is often blamed for the poor economic performance of many sub-Saharan countries. For instance, vote-buying may undermine accountability and the implementation of sound development policies by pressuring individuals to vote against their own interests. Yet, these effects depend on vote-buying leading to electoral outcomes that would not have occurred otherwise. In this paper, we use Afrobarometer survey data from 17 sub-Saharan elections between 2000 and 2005 to show that, despite its widespread prevalence, vote-buying has limited electoral impact: in only 6 out of 17 elections are gifts-for-votes practices associated with higher turnout than would be expected; yet, in only one election (Nigeria in 2003) did this higher turnout visibly translate into electoral advantage for a particular party. This contrasts with common perceptions about the effectiveness of electoral handouts and the apparent low quality of sub-Saharan African elections.
Keywords: C83; D72; O55; 330; national elections; electoral gifts; vote-buying; sub-Saharan Africa; survey analysis